1987
DOI: 10.1107/s0108270187093983
|View full text |Cite
|
Sign up to set email alerts
|

Localization of water in hexasodium hexakis(aluminosilicate)–deuterium oxide (1/8), Na6[AlSiO4]6.8D2O. A neutron powder diffraction Rietveld profile analysis at 10 K

Abstract: (4)]11. These findings are contrary to the behaviour of the water molecules in the basic sodalites Naa[A1SiO416(OH)2.nH20, 0 < n < 4, which show no hydrogen bonding to the framework O atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…On the other hand, the reversible dehydration/hydration phenomena and the consequent anomalous effect on framework geometry are only known from hydro sodalites [7,11,12]. Although very many hydro sodalites have been reported within a vast range of chemical compositions, their compositional variations were mostly confined to either topotactic manipulation of the guest species or complete replacement of the framework T-atoms [7,[11][12][13][14][15][16][17][18]. In contrast, partial T-sites substitution in the sodalite frameworks [19][20][21][22] remains little explored whereas extensive commercial successes have been achieved through partial T-sites substitution in zeolites [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the reversible dehydration/hydration phenomena and the consequent anomalous effect on framework geometry are only known from hydro sodalites [7,11,12]. Although very many hydro sodalites have been reported within a vast range of chemical compositions, their compositional variations were mostly confined to either topotactic manipulation of the guest species or complete replacement of the framework T-atoms [7,[11][12][13][14][15][16][17][18]. In contrast, partial T-sites substitution in the sodalite frameworks [19][20][21][22] remains little explored whereas extensive commercial successes have been achieved through partial T-sites substitution in zeolites [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The position of the last hydrogen could not be established [40]. In this structure there is effectively no hydrogen bonding between the OH and H 2 O moieties with the framework oxygen [31].…”
Section: Discussionmentioning
confidence: 94%
“…As a result each cage in the sodalite structure contains four Na, one OH, and two H 2 O species. Different authors have reported on the positional variations of oxygen, hydrogen, and the sodium in hydroxy sodalite upon partial and full loss of framework water [39][40][41]. In the fully hydrated form the tetrahedrally coordinated Na cations are located close to the 6-membered ring faces on the corners of a cubical structure as presented in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Shannon et al, using both classical force field energy minimization and DFT methods, report a similar result. Felsche and Luger, writing at least five articles in the mid-1980s, have probably contributed the most toward our understanding of Na 6 [SOD]·(H 2 O) n . ,,, In the end, two independent, experimental studies 33,45 were chosen by which to validate the simulation results.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas most sodalite materials contain eight monovalent cation (M + ) and two monovalent anion species (X - ), the so-called “class A” sodalites, this study examines a particularly unique sodalite materialNa 6 [SOD]·(H 2 O) n . First reported as a “sodium poor”' sodalite in 1947 by Borchert and Keidel, the presence of only six extraframework cations invokes unique unit cell distortions and asymmetric ring configurations for which considerable adsorption and exchange properties have been reported …”
Section: Sodalite Structurementioning
confidence: 99%